Longitudinal associations of total and trunk fat in childhood and adolescence and risk of hepatic steatosis at 24 years. - Cohen, Catherine C.; Sekkarie, Ahlia; Figueroa, Janet; Gillespie, Scott E.; Vos, Miriam B.; Welsh, Jean A. (Pediatric Obesity, 2021)
Summary: Background: The importance of body fat distribution in the development of nonalcoholic fatty liver disease (NAFLD) is unclear. Objective: To examine whether total and truncal fat deposition patterns in childhood/adolescence are associated with NAFLD risk at 24 years. Methods: Data were from 1657 participants in the Avon Longitudinal Study of Parents and Children. Transient elastography was used to assess hepatic steatosis (low/moderate/severe) at 24 years and dual‐energy X‐ray absorptiometry was used to assess total body fat percent (TBF%) and trunk fat percent (TrF%) at 9, 13, 15, 17, and/or 24 years. Linear mixed models were constructed with quadratic age to examine trajectories of TBF% and TrF% by steatosis at 24 years, adjusting for confounders. Results: In both sexes, TBF% trajectories from 9 to 24 years followed a similar pattern based on steatosis group (P =.83 for boys and P =.14 for girls for age2*steatosis fixed effect). However, at all ages TBF% was higher for moderate/severe vs low steatosis at 24 years (P <.05). In contrast, TrF% trajectories diverged based on steatosis group (P =.001 for boys and P =.0002 for girls for age2*steatosis fixed effect), such that, in both sexes, participants with moderate/severe steatosis at 24 yrs exhibited less decline in TrF% from adolescence to adulthood compared to participants with low steatosis at 24 yrs. Similar to TBF%, TrF% was higher at nearly all ages for moderate/severe vs low steatosis. Results were similar after adjusting for BMI category at each age, except in boys some differences for TrF% were attenuated. Conclusions: These findings suggest that sex‐specific body fat distribution patterns in childhood/adolescence may help to identify those at risk of developing NAFLD in adulthood.